Occupational Therapy in Children with Special Needs: Systematic Review - Asya, Ulul Azmi; Huriati; Amal, Andi Adriana; Arbianingsih (Universitas STRADA Indonesia, 2020)
Background: Children with special needs are children who are significantly different from other children, they are physically, psychologically, cognitively and socially obstructed in achieving their goals and potential to the fullest such as autism.Purpose: This study aimed to determine the provision of effective occupational therapy in children with special needs.Methods: This research uses a quantitative descriptive design. Search for research articles in several databases using certain keywords in the period 2015-2019.Results: Search results obtained 1396 articles using occupational therapy, there were only 10 articles that met the inclusion criteria analyzed using the Duffy's Research Appraisal Checklist Approach and the 10 articles included in the superior paper category so that it was good for further analysis. Based on the results of Systematic Review shows that effective occupational therapy is given to children with special needs (Autism). Occupational therapy given is very varied, namely drawing, collage technique, buttoning clothes, remembering pictures, sensory oral motor stimulation. Motor skills acquisition training, Equine-Assisted Therapy / EAT, Sensory Integration Therapy / SIT.Conclusion: From the analysis of the article shows that all occupational therapy can help improve both physical and mental development in children with autism so that children with autism can carry out daily activities like children in general and improve their quality of life. Occupational therapy found in this review can be used as an intervention in overcoming Developmental problems in children with autism due to simple techniques using daily activities